THE PROFILE OF THYROTROPIN-RELEASING HORMONE, T-REGULATOR, AND INTERLEUKIN-4 OF UNTREATED GRAVES’ DISEASE IN INDONESIA - DECROLI, EVA; ELVIRA, DWITYA; APRILIA, DINDA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: This study was conducted to the profile of hormonal and immunological aspects, which is thyrotropin-releasing hormone (TRH), T-regulator (T-reg) Forkhead box P3 (FOXP3) gene polymorphism, and interleukin-4 (IL-4) of untreated Graves’ disease with hyperthyroid in M Djamil General Hospital Padang, Indonesia. Methods: A cross-sectional study was conducted to observe Graves’ disease with hyperthyroid in the Internal Medicine Department in Dr. M. Djamil Hospital, Padang, West Sumatera, Indonesia. Graves’ disease was confirmed by measuring free thyroxine (FT4), thyroid-stimulating hormone (TSH), and antithyroid peroxidase (anti-TPO). TRH, T-reg FOXP3 gene polymorphism, and IL-4 were examined with an enzyme-linked immunosorbent assay method. Results: Twenty-five subjects with Graves’ disease included in this study with an average of age is 27.48 (5.6) years. Mean Wayne index is 23.44 (1.4), mean serum FT4 level is 55.55 (17.98) pmol/l, median serum TSH level is 0.041 (0.004–0.053) mU/l, and mean anti-TPO level is 2697.539 (479.72) pg/ml. Median serum TRH level is 92.589 (24.843–253.186) pg/ml, mean T-reg FOXP3 gene polymorphism is 0.621 (0.23) ng/ml, and mean serum IL-4 level is 19.759 (7.03) pg/ml). Conclusion: Graves’ disease with hyperthyroid has median serum TRH level 92.589 (24.843-253.186) pg/ml and high levels of T-reg FOXP3 gene polymorphism and IL-4.